Women over 40, foreigners of color, and other missing persons in globalizing mediascapes: understanding marketing images as mirrors of intersectionality. Issue 4 (4th July 2018) - Gopaldas, Ahir; Siebert, Anton
ABSTRACT: Media diversity studies regularly invoke the notion of marketing images as mirrors of racism and sexism. This article develops a higher-order concept of marketing images as "mirrors of intersectionality." Drawing on a seven-dimensional study of coverperson diversity in a globalizing mediascape, the emergent concept highlights that marketing images reflect not just racism and sexism, but all categorical forms of marginalization, including ableism, ageism, colorism, fatism, and heterosexism, as well as intersectional forms of marginalization, such as sexist ageism and racist multiculturalism. Fueled by the legacies of history, aspirational marketing logics, and an industry-wide distribution of discriminatory work, marketing images help to perpetuate multiple, cumulative, and enduring advantages for privileged groups and disadvantages for marginalized groups. In this sense, marketing images, as mirrors of intersectionality, are complicit agents in the structuration of inequitable societies.